Dinamika tingkat kemandirian pangan: implikasinya terhadap kebijakan ketahanan pangan nasional: The dynamics of food resilience: implications for national food security policy - Wahida; Perdana, Resty Puspa; Septanti, Kartika Sari; Suryana, Esty Asriyana; Ulpah, Amalia; Raharjo, Agus Saras Sri; Suharyono, Sri; Yuliani, Fitria (Analisis Kebijakan Pertanian, 2025)
Food resilience refers to a country’s ability to produce a diverse range of foods, ensuring its entire population has sufficient food at affordable prices. National food self-sufficiency is crucial in addressing various national and global shocks to the food system. This paper analyzes the development of food resilience in aggregate and for several strategic commodities, providing a reference for writing policy recommendations to achieve food security. The study was conducted from July to December 2023 using secondary data from the Food and Agriculture Organization (FAO)’s food balance sheets from 1961 to 2021. Study results show that Indonesia’s food resilience has a downward trend, indicated by a decreasing share of food availability from domestic production, which may threaten the stability of food supply and prices due to import dependency. To strengthen food resilience, production must be increased by improving access to agricultural inputs, optimizing the use of marginal land, revising land protection policies, expanding farmers’ access to technology, encouraging youth involvement in agriculture, and ensuring fair commodity prices that support farmer welfare. Specific strategies to increase production are applying agroecological practices for rice, revitalizing dryland irrigation for corn, enhancing cold-chain logistics for beef, protecting small-scale poultry farmers, and modernizing sugar factories. Additionally, the government needs to accelerate the diversification of food consumption and production based on local food sources and strengthen micro, small, and medium-scale enterprises (MSMEs) in food processing.